Digitalization of China’s Economy: Risks and Opportunities for Society - Lilia V. Tomaichuk (Евразийская интеграция: экономика, право, политика, 2019)
In recent years, China has gone through a rapid growth in digitalization of national economy, mainly in such areas as e-commerce, fi nancial technology, and manufacturing. Elements of the digital economy increasingly fulfi l the daily lives of citizens. The article is dealing with the phenomenon of digitalization of the economy in Chinese society. The administrative structure governing technological areas, and the regulatory legislative basis have been analyzed. The political, economic, social factors of digitalization growth and the problems restraining the digitalization process in China are underlined. Beijing aims to strengthen technological capabilities and achieve the level of developed countries. On this path, it is important to provide “analogue additions”, in particular, to improve legislation that provides innovation and competition, to bring the qualifications into line with the requirements of the new economy, to provide social guarantees.